Effects of dandelion root on rat heart function and oxidative status - Kristina Radoman; Vladimir Zivkovic; Nebojsa Zdravkovic; Natalia Vasilievna Chichkova; Sergey Bolevich; Vladimir Jakovljevic (BMC, 2023)
Abstract This study aimed to examine the effects of dandelion root on rat heart function and oxidative status. At the beginning of the experimental protocol, Wistar albino rats were randomly classified into two groups (10 rats per group): 1. control group - animals that drank tap water; 2. experimental group - animals that drank dandelion root for four weeks. Every morning for four weeks, the animals received freshly boiled dandelion root in a volume of 250 ml. At the end of the dandelion administration, animals were sacrificed, and their hearts were isolated and retrogradely perfused according to the Langendorff technique at a gradually increasing perfusion pressure between 40 - 120 cm H2O. The following myocardial function parameters were measured: maximum rate of left ventricular pressure development (dp/dt max), minimum rate of left ventricular pressure development (dp/dt min), systolic left ventricular pressure (SLVP), diastolic left ventricular pressure (DLVP), heart rate (HR). In addition, the coronary flow (CF) was measured flowmetrically. Finally, blood samples were collected after sacrificing to determine oxidative stress biomarkers: nitrite (NO2 −), superoxide anion radical (O2 −), hydrogen peroxide (H2O2), the index of lipid peroxidation (TBARS), reduced glutathione (GSH), catalase (CAT) and superoxide dismutase (SOD). The present pioneer results indicated that dandelion root did not manifest a negative impact on functional aspects of isolated rat heart. In addition, dandelion consumption was not associated with promising results in terms of maintaining systemic redox balance.